Validation of a Flow Cytometry Live Cell-Based Assay to Detect Myelin Oligodendrocyte Glycoprotein Antibodies for Clinical Diagnostics. (30th October 2021) - Lopez, Joseph A; Houston, Samuel D; Tea, Fiona; Merheb, Vera; Lee, Fiona X Z; Smith, Sandy; McDonald, David; Zou, Alicia; Liyanage, Ganesha; Pilli, Deepti; Denkova, Martina; Lechner-Scott, Jeannette; et al.
Abstract: Background: Myelin oligodendrocyte glycoprotein antibodies (MOG Ab) are essential in the diagnosis of MOG Ab–associated disease (MOGAD). Live cell-based assays (CBAs) are the gold standard for MOG Ab detection with improved sensitivity and specificity over fixed CBAs. A number of testing centers have used flow cytometry for its high throughput and quantitative utility. Presently, there is increasing demand to translate these research-based methods into an accredited routine diagnostic setting. Methods: A flow cytometry live CBA was used to detect MOG Ab in patients with demyelination. Serostatuses were compared between a research-based assay and a streamlined diagnostic assay. Inter-laboratory validation of the streamlined assay was performed in an accredited diagnostic laboratory. Further streamlining was performed by introducing a borderline serostatus range and reducing the number of controls used to determine the positivity threshold. Results: High serostatus agreement (98%–100%) was observed between streamlined and research-based assays. Intra- and inter-assay imprecision was improved in the streamlined assay (mean intra- and inter-assay CV = 7.3% and 27.8%, respectively) compared to the research-based assay (mean intra- and inter-assay CV = 11.8% and 33.6%, respectively). Borderline positive and clear positive serostatuses were associated with confirmed phenotypes typical of MOGAD. Compared to using 24 controls, robust serostatus classification was observed when using 13 controls without compromising analytical performance (93%–98.5% agreement). Conclusions: Flow cytometry live CBAs show robust utility in determining MOG Ab serostatus. Streamlining and standardizing use of this assay for diagnostics would improve the accuracy and reliability of routine testing to aid diagnosis and treatment of patients with demyelination.